1987
DOI: 10.1111/j.1432-1033.1987.tb10564.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis in Drosophila melanogaster embryos

Abstract: Eukaryotic initiation factor 2 (eIF-2) was purified from the high-salt wash fraction of Drosophilu melunoguster embryos. This factor, with a molecular mass of about 90 kDa, consists of two subunits of 47 kDa and 39 kDa on dodecylsulfate/polyacrylamide gel electrophoresis. The 39-kDa subunit is phosphorylated by the hemin-controlled inhibitor of rabbit reticulocytes in a terminal fragment which can be cleaved by mild treatment with trypsin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The identity of the band as eIF2␣ was confirmed by comparison with the positions of mammalian and D. melanogaster eIF2␣ (probed with antibodies specific for the respective proteins). This confirms the earlier finding that D. melanogaster eIF2␣ is a substrate for HRI (15). PKR was also able to phosphorylate eIF2␣ in extracts of Schneider cells (data not shown).…”
Section: Schneider Cell Extracts Display Eif2b Activity Which Issupporting
confidence: 81%
See 1 more Smart Citation
“…The identity of the band as eIF2␣ was confirmed by comparison with the positions of mammalian and D. melanogaster eIF2␣ (probed with antibodies specific for the respective proteins). This confirms the earlier finding that D. melanogaster eIF2␣ is a substrate for HRI (15). PKR was also able to phosphorylate eIF2␣ in extracts of Schneider cells (data not shown).…”
Section: Schneider Cell Extracts Display Eif2b Activity Which Issupporting
confidence: 81%
“…The affinity of eIF2 for GDP at physiological magnesium concentrations was such that a mechanism of catalysis would be required to form the active eIF2⅐GTP complex (13,14). However, Mateu and colleagues (13,15) reported that nucleotide exchange on D. melanogaster eIF2 was independent of an exchange factor under several conditions. Moreover, no guanine nucleotide exchange activity for eIF2 in D. melanogaster was detected in embryos (14).…”
mentioning
confidence: 99%
“…The total amount of this protein usually obtained from the postribosomal supernatant and the ribosomal highsalt wash of 100 g (wet weight) of embryos is about 180 ,ug. From this and the known values (25) of the mass of a wet embryo (20 ,ug) and the water space of an embryo (8 nl), a mean concentration of 130 nM can be inferred. Estimating a concentration of 80S ribosomes per embryo of about 1.8 ,uM (data not shown), we obtain a 35-kDa CBP-to-ribosome ratio of approximately 0.07.…”
Section: Discussionmentioning
confidence: 99%
“…However, to enable detailed study of mechanism of this control, the need to characterize the CBPs from this organism became evident (23). Such studies would also be of interest in elucidating the translational initiation mechanism in a eucaryote evolution-2182 MAROTO AND SIERRA ary distant from mammals, a goal we have already begun to pursue (24,25).…”
mentioning
confidence: 99%
“…Drosophila eIF4E has been shown previously to be enriched in the post-ribosomal supernatant compared with ribosomal high salt wash (Maroto and Sierra, 1989). Post-ribosomal supernatants were prepared essentially as described previously (Mateu et al, 1987;Webster et al, 1991). Briefly, the * This work supported by a grant from the Medical Research Council of Canada (to P. L. and N. S.).…”
Section: Methodsmentioning
confidence: 99%